Representation of the concept «Native land» in the works of Zhumeken Nazhimedenov (Eurasian Journal of Philology Science and Education, 2019)
In this article, we chose our own names as an object of study, including onyms that appear withinthe framework of the linguocultural concept «Tugan zher» that we are considering, and linguistic unitsthat recreate the national genetic code directly related to human knowledge, and dwell on the work ofan outstanding poet Zhumekena Najmendenova for the representation of the concept of the concept of«native land» from the standpoint of nationalassociative and author’s perception.